2016
DOI: 10.1007/978-1-4939-6533-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Chromoplasts and Suborganellar Compartments from Tomato and Bell Pepper Fruit

Abstract: Tomato is a model for fruit development and ripening. The isolation of intact plastids from this organism is therefore important for metabolic and proteomic analyses. Pepper, a species from the same family, is also of interest since it allows isolation of intact chromoplasts in large amounts. Here, we provide a detailed protocol for the isolation of tomato plastids at three fruit developmental stages, namely, nascent chromoplasts from the mature green stage, chromoplasts from an intermediate stage, and fully d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…In US alone, tomatoes are a $2.2 billion industry. Tomato is a model system for studying fruit development [118] and recent insights into the dynamics of the tomato's plastid proteome during the differentiation of chloroplasts to chromoplasts have provided important insights in these processes [47,48,51]. In addition, tomato is a model system for the study of the induction of plant defenses associated with wounding, herbivory and pathogen attack [119].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In US alone, tomatoes are a $2.2 billion industry. Tomato is a model system for studying fruit development [118] and recent insights into the dynamics of the tomato's plastid proteome during the differentiation of chloroplasts to chromoplasts have provided important insights in these processes [47,48,51]. In addition, tomato is a model system for the study of the induction of plant defenses associated with wounding, herbivory and pathogen attack [119].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous methods for isolation of intact plastids and sub-fractionation of chloroplast compartments for proteomics studies in Arabidopsis populate our literature today [42,46,84]. In addition, robust methods have been developed for isolation of metabolomics-and proteomics-grade chromoplasts of tomato fruit [47][48][49][50][51]58] (Additional file 1: Table S1). While protocols for isolating chloroplasts for DNA isolation, enzymatic assays and protein import assays have been described [53][54][55][56][57]85], rather surprisingly, few chloroplast large-scale proteomics studies have been reported for tomato leaves [52] (Additional file 1: Table S1).…”
Section: Overview Of the Tomato Chloroplast Isolation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most commonly used methods is the sucrose gradient. This method is applied on a crude extract of tomato chromoplast which is prepared from around 300 g of tomato fruits subjected to a series of washes, grinding, filtering, and centrifugation steps (Barsan et al 2017). The crude chromoplast suspension is layered on top of the sucrose gradient and subjected to centrifugation allowing the different organelles to be localized in the different fractions (e.g.…”
Section: Plastid Proteomics: From Chloroplast Isolation To Mass Spectmentioning
confidence: 99%
“…Isolation of plastids is a prerequisite for the in-depth study of plastid function during citrus fruit ripening. Although there are studies for plastid isolation in limited plant species, including those using sucrose gradient to isolate chromoplasts and suborganellar compartments in different vegetables [ 19 , 20 ] and that using Nycodenz density gradient for plastid isolation in tomato [ 21 ] and sweet orange pulp [ 18 ], isolation of chloroplasts or chromoplasts from the peel of citrus fruit is still very challenging due to the presence of large amounts of essential oils and acidic juices in the fruit. In this work, we identified a citrus variety, the ‘Hua Pi’ kumquat ( Fortunella crassifolia Swingle), whose oil-free property greatly reduces the difficulty of plastid isolation from citrus peel.…”
Section: Introductionmentioning
confidence: 99%